Cook, Noble David, con Alexandra Parma Cook. People of the Volcano. Andean Counterpoint in the Colca Valley of Peru. Durham and London: Duke University Press, 2007, xvi + 319 pp., ilustr. - Flores Espinoza, Javier (2008)
La reseña no presenta resumen.